International evidence on firm level decisions in response to the crisis: shareholders vs. other stakeholders - Allen,HF; Carletti,E; Grinstein,Y (Journal of the Japanese and International Economies, 2018)
The relationship between changes in GDP and unemployment during the 2008 financial crisis differed significantly from previous experiences and across countries. We study firm-level decisions in France, Germany, Japan, the UK, and the US. We find significant differences between the response of US and non-US firms. US firms significantly decreased their production costs relative to firms in other countries. They have also reduced debt, reduced dividend payout, and increased their cash holdings compared to firms in other countries. The differences are, in general, explained by differences in financial leverage. However, financial leverage does not explain differences between production decisions in German and U.S. firms and between Japanese and US firms. We argue that differences in firm governance between US firms and firms in Germany and Japan drive these responses. US firms are more prone to cut labor costs and reduce leverage compared to German firms and Japanese firms in order to achieve larger profits and a larger cash-cushion in the short-run.